Scaling up self-stratifying supercapacitive microbial fuel cell - Walter, Xavier Alexis (Int J Hydrogen Energy, 2020)
Self-stratifying microbial fuel cells with three different electrodes sizes and volumes were operated in supercapacitive mode. As the electrodes size increased, the equivalent series resistance decreased, and the overall power was enhanced (small: ESR = 7.2 Ω and P(max) = 13 mW; large: ESR = 4.2 Ω and P(max) = 22 mW). Power density referred to cathode geometric surface area and displacement volume of the electrolyte in the reactors. With regards to the electrode wet surface area, the large size electrodes (L-MFC) displayed the lowest power density (460 μW cm(−2)) whilst the small and medium size electrodes (S-MFC, M-MFC) showed higher densities (668 μW cm(−2) and 633 μW cm(−2), respectively). With regard to the volumetric power densities the S-MFC, the M-MFC and the L-MFC had similar values (264 μW mL(−1), 265 μW mL(−1) and 249 μW cm(−1), respectively). Power density normalised in terms of carbon weight utilised for fabricating MFC cathodes-electrodes showed high output for smaller electrode size MFC (5811 μW g(−1)-C- and 3270 μW g(−1)-C- for the S-MFC and L-MFC, respectively) due to the fact that electrodes were optimised for MFC operations and not supercapacitive discharges. Apparent capacitance was high at lower current pulses suggesting high faradaic contribution. The electrostatic contribution detected at high current pulses was quite low. The results obtained give rise to important possibilities of performance improvements by optimising the device design and the electrode fabrication.